Evaluation of a Mobile Application for Cognitive Training in Healthy Adults - Giannopoulou, Panagiota; Vlamos, Panayiotis; Papalaskari, Mary-Angela (International Journal of Interactive Mobile Technologies (iJIM), 2023)
In the face of the increasing prevalence of neurodegenerative disorders and the lack ofeffective treatments, there is growing interest in non-pharmacological approaches forcognitive decline. Mobile applications have emerged as a promising tool for detecting cognitivedisorders, providing patient training, and enhancing cognitive performance. However,the availability of applications that integrate comprehensive cognitive training, memorydeficit analysis, and cognitive status monitoring across various domains for the adult populationremains limited. To address this gap, the Rodi application was developed and piloted with24 adults. The usability, usefulness, viability, and efficacy of the app were evaluated, alongwith its preliminary effectiveness. The results indicated high ratings for usability (4.53/5.00),usefulness (4.63/5.00), viability (4.5/5.00), and efficacy (4.08/5.00). Moreover, aligned withprevious research, the present study yielded findings indicating that younger participantsachieved significantly higher scores and completed cognitive tasks in shorter times as comparedto their older counterparts. Finally, the results of the current study findings underscorethe potential of the RODI application to enhance cognitive abilities in a user-friendly andfamiliar setting. However, further large-scale evaluations are necessary to validate the app’seffectiveness and assess its broader impact.40865:With so many online information sources in recent years, it has become increasingly difficultto determine if the content is based on facts, half-truths, or lies. As a result, the goal of thisresearch is to propose a serious game design for learning to evaluate sources using the CRAAPtest. In the game, players take on the role of librarians who must evaluate news from socialmedia and newspapers, determine whether it is fake or true, and then inform the people ofthe city. During their efforts to make the correct decision, the players are able to observe andlearn about the impact of fake news on the community and the city as a result of their decisions.To evaluate the game, we did a randomized online field study, including quantitativeresearch based on pre-posttests involving 351 participants. The results revealed that using aserious game of “How to Spot Fake News” can improve the knowledge of information literacyneeded to evaluate online sources of information. Finally, we provide preliminary evidencethat gaming improves people’s ability to recognize and resist misinformation.